Liver Disease and Surgery - Tsoulfas, Georgios; Rodrigo, Luis (IntechOpen, 2019)
The goal of this book is to present a review of the different categories of liver disease, as well as address the role of surgery in managing these complex diseases. The book includes chapters written by international experts on the most current indications and guidelines regarding the diagnoses and management of liver diseases, as well as a variety of technical elements involved with the surgical procedures. Different surgical techniques involved in performing a hepatectomy will be discussed, including various instruments used, as well as the effect of modern technology as evidenced by novel procedures. An important focus of the book has been identifying the proper place of all these hepatectomy methods in the armamentarium of the experienced hepatobiliary surgeon, including the role of locoregional treatments such as ablation and embolization as adjuncts. Finally, the role of hepatectomy compared to orthotopic liver transplantation is discussed, so that the reader can have a well-rounded picture of the challenges and opportunities involved. Overall, this book has the potential to serve as an invaluable "tool" for both the hepatologist and the internist, as well as for the hepatic surgeon